H2B ubiquitylation modulates spliceosome assembly and function in budding yeast. (25th February 2014) - Hérissant, Lucas; Moehle, Erica A.; Bertaccini, Diego; Van Dorsselaer, Alain; Schaeffer‐Reiss, Christine; Guthrie, Christine; Dargemont, Catherine
<x xml:space="preserve">Abstract</x> Splicing occurs co‐transcriptionally for the vast majority of intron‐containing genes in the yeast Saccharomyces cerevisiae. Here, we analysed the contribution of transcription‐dependent chromatin marks on spliceosome assembly and function on nascent transcripts and found that multiple histone modifications, and in particular Ub‐H2B, are required for optimal spliceosome function at distinct subsets of genes. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>